"Even machines get a rest": the commodification of the H-2A Indigenous sheepherder in Colorado's Western Slope - Coenen, Shirley Man-Kin, author; Sagas, Ernesto, advisor; Souza, Caridad, committee member; Fernandez-Gimenez, Maria, committee member (Colorado State University. Libraries, 2018)
This project uses an exploratory, qualitative study to examine the ways in which the H-2A "guestworker" program in the United States is racialized and gendered as a temporary, state-controlled, foreign labor system. This project is accomplished through the exploration of testimonios of H-2A sheepherders in Colorado, and how these narratives are informed by race, class and the gendered identities of guestworkers. While there is significant descriptive work on labor and migration throughout U.S. history, there is a paucity of contemporary scholarship on guestworkers situated within a critical race and gendered lens. This work aims to bridge that gap by drawing from the conceptual frameworks within ethnic studies to integrate both race and gender. By analyzing patterns that emerge within the H-2A visa workers narratives, one can gain a perspective on the role of temporary guestworker programs in modern day transnational immigration practices. This leads to a basis for a theoretically grounded perspective on how race and gender influence modern guestworker labor practices.